Implementasi Program Tahfidz dalam Membentuk Karakter Siswa di MTs Negeri 3 Banyumas - Rizka Lutfiana; Yosi Intan Pandini Gunawan (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
Education is a process of internalizing values, knowledge, skills, and character formation towards becoming a better individual. In the era of globalization, various challenges arise such as moral degradation, misuse of technology, and the lack of students’ religiosity. These conditions encourage the need to strengthen character education based on the values of the Qur’an. One of the efforts made is through the tahfidz Al-Qur’an program, which aims not only to provide memorization skills but also to cultivate students’ religiosity and good character in line with the vision of the madrasah. This study aims to describe the implementation of the tahfidz Al-Qur’an program in shaping students’ character at MTs Negeri 3 Banyumas. The research employs a descriptive qualitative method with a field research approach conducted at MTs Negeri 3 Banyumas. Data were collected through observation, interviews, and documentation. The findings indicate that the implementation of the tahfidz program is carried out in three stages: (1) the planning stage, (2) the implementation stage, and (3) the evaluation stage. Specifically, the implementation at MTs Negeri 3 Banyumas also consists of three phases: (1) the preliminary stage, (2) the core stage, and (3) the closing stage. Meanwhile, the evaluation of students’ abilities is conducted through formative and summative assessments. The program has successfully shaped students’ character to become religious, disciplined, responsible, tolerant, resilient, independent, and honest. The challenges faced include differences in students’ memorization abilities and limited time, but these can be overcome through intensive guidance and support from both the school and parents. The Tahfidz program at MTs Negeri 3 Banyumas makes a significant contribution to character building, making it worthy of continuous development as part of Qur’an-based character education.